(untitled) (Literary Voice, 2024)
Myths rooted in patriarchal ideologies subordinate women and distort female experiences. They are laden with stereotypes and gendered representations. This raised a significant concern among feminist scholars to critically challenge narratives entrenched in patriarchal thought and carve new mythological grounds for women. Feminist writers have employed revisionist mythmaking strategies to articulate dissent and denounce myths that annihilate their experiences. The paper examines the revisionist strategies employed by Louise Gluck in her poem Circe’s Power (1996)from the collection Meadowlands (I996) using a feminist lens. The focus is on how Gluck reclaims and transforms the mythical landscape of the Odyssey, turning it into an empowered feminine space, thereby creating powerful connections between women and mythology. It pays close attention to the Greek character Circe from the Odyssey and explores how the poet appropriates her voice to subvert phallocentric mythic models, critiquing social expectations and gender roles. The study’s central focus is restoring Circe from the ruins of being trapped in her traditional archetypal role of the femme fatale.